Diagnosis and underdiagnosis of comorbidities in psoriasis patients - need for a multidisciplinary approach - Gleison Vieira Duarte; Maria de Fátima S. P. de Oliveira; Ivonise Follador; Thadeu Santo Silva; Edgar Marcelino de Carvalho Filho (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Psoriasis is an immune-mediated disease that manifests predominantly in the skin, although systemic involvement may also occur. Although associated comorbidities have long been recognized and despite several studies indicating psoriasis as an independent risk factor for cardiovascular events, little has been done in general medical practice regardind screening. In the United States, less than 50% of clinicians are aware of these recommendations. OBJECTIVE: To identify the prevalence of these comorbidities in 296 patients followed up at a university dermatology clinic. METHODS: Systematically investigated comorbidity frequencies were compared with general practitioners' registry frequencies. Clinical features correlated with comorbidities were also investigated. RESULTS: High prevalences of systematically investigated comorbidities such as hypertension (30%) and dyslipidemia (26.5%) were documented. Conversely, data from general practitioners' records showed that 33% of dyslipidemia cases were undiagnosed and indicated possible underdiagnosis of some comorbidities. Furthermore, an association was found between: the number of comorbidities and psoriasis duration, age and high body mass index an association was found between the number of comorbidities and psoriasis duration, age, high body mass index, waist circumference or waist-to-hip ratio. (p<0.05). CONCLUSION: Disease duration, age and high body mass index, waist circumference or waist-to-hip ratio are possible criteria for choosing which patients should be screened for comorbidities. Underdiagnosis of comorbidities by general practitioners highlights the need for a multidisciplinary approach in psoriasis management.